HEGEMONI KRITERIA ESTETIK: Tinjauan Sosiologi Sastra Atas Cerpen Pilihan Kompas dan Cerpen Kompas Pilihan - Adib Sofia (Jurnal Sosiologi Reflektif, 2015)
Hegemony is a concept introduced by Gramsci which has been widely used to examine political, cultural, and ideological forms His fundamental assertion is that there are complex and non mechanical links between culture and politics. He persistently questions what makes a certain cultural form become a common sense and valued ”high” or “low”, the effects of this division, and how such division is contemporarily reproduced CerpenKompasPilihan (Selected KompasShort Stories) and Cerpen Pilihan Kompas (Kompas Selected Short Stories) are selections of best short stories published by Kompas, a mainstream media corporation. They have been published periodically since 1970 and therefore considered an outstanding cultural form in the society. By employing Gramsci’s six key concepts, i.e culture, hegemony, ideology, popular beliefs, the intellectuals, and the state, this paper is aimed at examining (1) the selection process which involves valuing some of those pieces of writing as aesthetically “high” and some others as aesthetically “low”; and (2) the involvement of some elements of the society in the production process as well as in appreciating the best stories